Antimicrobial activity in vitro of latex from Jatropha multifida L. (Research, Society and Development, 2021)
Jatropha multifida L., popularly known as mertiolate, is a shrub whose red flowers with yellowish anthers look like small pieces of coral and a stem with latex presence. It is used in folk medicine to treat a variety of conditions, such as infected wounds, ulcers and dermatoses. The aim of the study was to verify the antimicrobial activity of in natura and lyophilized latex from J. multifida. It is a quantitative research, of the experimental type. The latex was collected in the city of Igreja Nova - Alagoas, using the bleeding method, in which oblique cuts were made on the stem, obtaining the extract in natura. To obtain the powdered extract, the lyophilization of the raw material was used. To evaluate the antimicrobial activity, the broth microdilution method was used to determine the Minimum Inhibitory Concentration (MIC), followed by plating on agar to obtain the Minimum Bactericidal Concentration (CBM) of the extracts against the microorganisms standardized by the American Type Culture Collection - ATCC: S. aureus (25923) S. epidermidis (31488), E. faecalis (29212), P. aeruginosa (27853), E. coli (25922), E. aerogenes (13048) and Minimum Fungicidal Concentration (MFM) for C . albicans (24433). The results showed that both J. multifida latex extracts showed moderate antimicrobial activity against most of the bacterial strains tested and a weak fungal activity against C. albicans, with emphasis on the lyophilized extract. It is concluded that the extracts were more promising against strains of S. aureus, S. epidermidis, E. faecalis and P. aeruginosa, opening up possibilities for further studies.